Tanggapan Masyarakat Kota Bandung terhadap Pesan Dakwah dalam Program Acara Percikan Iman di Radio Oz 103.1 FM Bandung - Adela Nur Rizkika; Muhammad Rahmat Effendi; Asep Ahmad Siddiq (Bandung Conference Series: Islamic Broadcast Communication, 2022)
Abstract. This research is a research broadcast da'wah through da'wah programs in radio mass media by examining the results of public responses, especially those in the city of Bandung, to the message of da'wah in the Sprinkling of Faith Program on Radio Oz 103.1 FM Bandung. The purpose of this study was to obtain data covering the contents of the Sprinkling Faith program, Radio listeners' responses to the da'wah message in the Sprinkling Iman program, supporting factors and obstacles for listeners of Radio Oz 103.1 FM Bandung to the Sprinkling Faith program. This study uses a descriptive quantitative method, using a purposive random sampling sample with a Likert scale, the sample size of this study was 30 respondents. Data collection techniques are questionnaires, interviews, observation, and literature study. The results of this study indicate that the Sprinkling of Iman program discusses the contents of the problem discussion material and book review. The limitation of this research material is the problem surgical material. Public Responses to the Sprinkling of Faith Program gave many positive responses, especially in improving the community's religious knowledge. The message of da'wah from the problem-solving material is the message of morality and the message of faith seen based on the source of the rebroadcast on the YouTube broadcaster/da'i media and analyzed. The constraint and supporting factors of this program are various that people complain about the lack of time, weather disturbances that can affect the quality of radio broadcasts, the supporting factors are presenting interactive broadcasts, speaking style and friendly and interesting announcers/da'i, knowledge of broadcasters/da'i when preaching is easy to understand, the clarity of articulation of the word announcer/preacher is clear. Abstrak. Penelitian ini adalah penelitian siaran dakwah melalui program dakwah di media massa Radio dengan meneliti hasil tanggapan Masyarakat khususnya yang berada di Kota Bandung terhadap pesan dakwah dalam Program Acara Percikan Iman di Radio Oz 103.1 FM Bandung. Tujuan penelitian ini yaitu untuk memperoleh data meliputi isi program Percikan Iman, tanggapan pendengar Radio terhadap pesan dakwah dalam program acara Percikan Iman, faktor pendukung dan faktor kendala pendengar Radio Oz 103.1 FM Bandung terhadap program acara Percikan Iman. Penelitian ini menggunakan metode kuantitatif deskriptif, dengan menggunakan sampel Purposive random sampling dengan skala Likert, Ukuran sampel penelitian ini 30 responden. Teknik pengumpulan data adalah kuesioner, wawancara, observasi, dan studi pustaka. Hasil penelitian ini menunjukkan bahwa program Percikan Iman membahas isi materi bedah masalah dan bedah buku. Pembatasan materi penelitian ini adalah materi bedah masalah. Tanggapan Masyarakat mengenai Program Acara Percikan Iman banyak memberi tanggapan positif terutama dalam peningkatan ilmu agama masyarakat. Pesan dakwah dari materi bedah masalah adalah pesan akhlak dan pesan akidah dilihat berdasarkan sumber siaran ulang di media youtube penyiar/da’i dan dianalisis. Faktor kendala dan pendukung dari program ini beragam bahwa masyarakat mengeluhkan waktu yang kurang, gangguan cuaca yang dapat mempengaruhi kualitas siaran Radio, faktor pendukungnya menyajikan siaran interaktif, gaya bicara dan penyiar/da’i yang ramah dan menarik, wawasan ilmu penyiar/da’i saat berdakwah mudah dipahami, kejelasan artikulasi kata penyiar/da’i yang jelas.